2017
DOI: 10.1016/j.jadohealth.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Continuity in Cannabis Use: The Role of Parent's Early Onset and Lifetime Disorder on Child's Early Onset

Abstract: Purpose Children's early onset of cannabis use was examined as a function of their parent's early onset of cannabis and subsequent incidence of a lifetime cannabis abuse or dependence disorder. Methods Prospective, longitudinal data from the Rochester Youth Development Study (RYDS) and the Rochester Intergenerational Study (RIGS) for 442 parent-child dyads (274 father-child, 168 mother-child) were utilized. The children were evenly split by sex. Logistic regression models and a path analysis were estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
5
35
1
1
Order By: Relevance
“…It is well documented that parenting behaviors vary for mothers and fathers (e.g., Craig, 2006) and for sons and daughters (e.g., Hagan, Gillis, & Simpson, 1990). Evidence also indicates that the antisocial behavior of fathers and mothers differentially affect children with evidence of greater continuity in antisocial behavior between fathers and their children compared to mothers and their children (Auty, Farrington, & Coid, 2015; see also Henry & Augustyn, 2016). The sources of continuity may also vary, which is in line with research conducted by Thornberry and colleagues (2003a) who found a direct relationship between parent adolescent delinquency and child delinquency among fathers and evidence for partial mediation through parenting behaviors, but this same relationship was entirely mediated by parenting behaviors among mothers.…”
Section: Current Studymentioning
confidence: 99%
“…It is well documented that parenting behaviors vary for mothers and fathers (e.g., Craig, 2006) and for sons and daughters (e.g., Hagan, Gillis, & Simpson, 1990). Evidence also indicates that the antisocial behavior of fathers and mothers differentially affect children with evidence of greater continuity in antisocial behavior between fathers and their children compared to mothers and their children (Auty, Farrington, & Coid, 2015; see also Henry & Augustyn, 2016). The sources of continuity may also vary, which is in line with research conducted by Thornberry and colleagues (2003a) who found a direct relationship between parent adolescent delinquency and child delinquency among fathers and evidence for partial mediation through parenting behaviors, but this same relationship was entirely mediated by parenting behaviors among mothers.…”
Section: Current Studymentioning
confidence: 99%
“…Despite these increases in cannabis use and CUD, attitudes towards cannabis use have softened: adult and adolescent perceptions of cannabis use risk have decreased since 2001 (Hasin et al 2015 ; Carliner et al 2017 ). These shifting attitudes have intergenerational consequences as offspring of parents who are early-onset cannabis users and who meet criteria for CUD are more likely to become early-onset cannabis users themselves (Henry and Augustyn 2017 ). With increases in cannabis use and decreases in perceived risk, it is necessary to reevaluate the addictive potential of cannabis (Carliner et al 2017 ; Hasin 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that parental cannabis use is associated with increased risk of adolescent use (Henry & Augustyn, 2017;Hill et al, 2018;Kosty et al, 2015), but few studies have examined the mechanisms underlying this relation. One proposed mechanism is parenting behaviors that are intended to deter adolescent substance use, including setting rules against substance use, discussing reasons not to use substances, and sharing personal negative experiences with substance use.…”
mentioning
confidence: 99%